Gender and civilian victimization in war - Peet, Jessica L. (Routledge studies in gender and security, 2020)
This book explores the role of gender in influencing war-fighting actors' strategies towards the attack or protection of civilians. Traditional narratives suggest that killing civilians intentionally in wars happens infrequently, and that the perpetration of civilian targeting is limited to aberrant actors. Recently, scholars have shown that both state and non-state actors target civilians, even while explicitly deferring to the civilian immunity principle. This book fills a gap in the accounts of how civilian targeting happens, and shows that these actors are in large part targeting women rather than some gender-neutral understanding of civilians. It presents a history of civilian victimization in wars and conflicts, and then lays out a feminist theoretical approach to understanding civilian victimization. It explores the British Blockade of Germany in World War I, the Soviet 'Rape of Berlin' in World War II, the Rwandan genocide, and the contemporary conflict in northeast Nigeria. Across these case studies, the authors lay out how gender is key to how war-fighting actors understand both themselves and their opponents, and therefore plays a role in shaping strategic and tactical choices. It makes the argument that seeing women in nationalist and war narratives is crucial to understanding when and how civilians come to be targeted in wars, and how that targeting can be reduced.